Something's wrong! : a bear, a hare, and some underwear - John, Jory (Farrar Straus Giroux Books for Young Readers/Macmillan Children's Publishing Group, 2021)
Jeff the bear is sure he has forgotten something when he sets out from home, but none of the animals he meets initially inform him that he is only wearing his underwear, until he reaches his friend Anders the hare--who quickly thinks of a way to avoid embarrassing Jeff, by starting a fashion trend.